Due citazioni dal Timeo in Michele Psello e il Commento al Timeo di Proclo. Prime osservazioni su Philosophica minora II 4-5. - Menchelli, Mariella (Medioevo Greco, 2016)
This paper focuses on Michael Psellus as reader of Plato's Timaeus and of Proclus' Commentary thereon. Particular attention is given to his writings PHI 73 and PHI 74 (while PHI 72 deserves further study). The author suggests that Psellus quoted from a manuscript with Proclus' works as well from a Plato manuscript, which cannot be identified with the Xlth century copy Tubingensis Mb 14, but might have been close (or equal) to the «deperditus g» Jonkers.